2013
DOI: 10.1007/s10620-013-2914-4
|View full text |Cite
|
Sign up to set email alerts
|

Dilation-Assisted Stone Extraction: An Alternative Method for Removal of Common Bile Duct Stones

Abstract: Dilation-assisted stone extraction and EST are safe and effective techniques for the treatment of CBD stones. Dilation-assisted stone extraction has high efficiency. This technique is an alternative method for removal of CBD stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 19 publications
3
37
0
11
Order By: Relevance
“…-: 2015 GASTROINTESTINAL ENDOSCOPY 5 success rate in EPLBD with EST was similar to that of EST alone in 1 retrospective cohort study, 20 in 4 of the 6 randomized, controlled trials [27][28][29][30] ; and in all 5 meta-analyses 16,[31][32][33]36 ; whereas it was significantly higher in EPLBD with EST than that in EST alone in another 2 retrospective cohort studies by Kim et al 25 and Rosa et al 26 and the remaining 2 randomized, controlled trials by Li at al 34 and Jun et al 35 The overall success rate of EPLBD with EST in the previously mentioned systematic review 18 was comparable to that of EST alone (96.5% vs 95.3%, P Z .141) in a previous meta-analysis. 11 The overall success rate of EPLBD with EST was similar to that of EST alone in 2 of 3 retrospective cohort studies 20,25 ; in all 6 randomized, controlled trials [27][28][29][30]34,35 and in all 5 meta-analyses, 16,[31][32][33]36 whereas it was significantly higher in EPLBD with EST than in EST alone in the remaining retrospective cohort study by Rosa et al 26 Based on these results, the initial and overall success rates of EPLBD with EST are comparable to, or somewhat better than, those of EST alone.…”
Section: The Balloon Should Be Inflated Slowly In Gradual Stepsmentioning
confidence: 71%
See 2 more Smart Citations
“…-: 2015 GASTROINTESTINAL ENDOSCOPY 5 success rate in EPLBD with EST was similar to that of EST alone in 1 retrospective cohort study, 20 in 4 of the 6 randomized, controlled trials [27][28][29][30] ; and in all 5 meta-analyses 16,[31][32][33]36 ; whereas it was significantly higher in EPLBD with EST than that in EST alone in another 2 retrospective cohort studies by Kim et al 25 and Rosa et al 26 and the remaining 2 randomized, controlled trials by Li at al 34 and Jun et al 35 The overall success rate of EPLBD with EST in the previously mentioned systematic review 18 was comparable to that of EST alone (96.5% vs 95.3%, P Z .141) in a previous meta-analysis. 11 The overall success rate of EPLBD with EST was similar to that of EST alone in 2 of 3 retrospective cohort studies 20,25 ; in all 6 randomized, controlled trials [27][28][29][30]34,35 and in all 5 meta-analyses, 16,[31][32][33]36 whereas it was significantly higher in EPLBD with EST than in EST alone in the remaining retrospective cohort study by Rosa et al 26 Based on these results, the initial and overall success rates of EPLBD with EST are comparable to, or somewhat better than, those of EST alone.…”
Section: The Balloon Should Be Inflated Slowly In Gradual Stepsmentioning
confidence: 71%
“…In the systematic review, which included 30 studies conducted in patients with EPLBD with EST, the rate of overall adverse events was significantly lower for EPLBD with EST than that for EST alone (8.3% vs 12.7%, OR 1.60, P < .001). 18 The rate of overall adverse events was similar in 5 of all 6 randomized, controlled trials between the 2 groups, 27,28,30,34,35 whereas it was significantly lower for EPLBD with EST than that for EST alone in the remaining study by Stefanidis et al 29 In contrast, in 4 of 5 metaanalyses that evaluated a comparison of EPLBD with EST and EST alone in the removal of large bile duct stones, the rate of overall adverse events was significantly lower for EPLBD with EST than that for EST alone. 16 large-scale multicenter case-control study that investigated 946 patients, a subgroup analysis showed that stones larger than 16 mm, cirrhosis, and full-length EST were independently associated with an increase in overall adverse events.…”
Section: 2mentioning
confidence: 88%
See 1 more Smart Citation
“…Endoscopic papillary balloon dilation (EPBD) has been advocated as an alternative to EST because it is widely believed that this approach can preserve the function of the biliary sphincter, thus decreasing the incidence of hemorrhage and perforation as compared with EST [6][7][8][9]. Nevertheless, EPBD is only effective for removal 1 3 of small to moderate bile duct stones (less than 8 mm in diameter) due to the biliary opening being smaller than that with EST [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…La EFT es inicialmente recomendada como paso previo a la DPBG, ya que se cree que está asociada con una disminución del riesgo de pancreatitis posprocedimiento (Figura 2) (8,9,13,14). Puede utilizarse como método inicial cuando se documentan cálculos gigantes en las imágenes o cuando la remoción convencional con EFT y canastilla han fallado (14,15,16).…”
Section: Resultsunclassified